Super selective intra-arterial cerebral infusion (SSIACI) for newly diagnosed and recurrent glioblastoma - Syed Sarmad Bukhari; Noman Ahmed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
Chemotherapy with various modalities is the standard of care in the management of newly diagnosed and recurrent glioblastoma. Current guidelines recommend intravenous administration of systemic chemotherapy. However, the blood brain barrier (BBB) restricts ionized molecules larger than 180 Da (Daltons) while most chemotherapeutic agents are between 200-1200 Da (TMZ [194 Da]). The doses administered are restricted by their systemic toxicity. Super selective intra-arterial cerebral infusion (SSIACI) can administer a localized regular or higher dose of chemotherapy that circumvents the systemic circulation. This is accompanied by disruption of the BBB (BBBd) which can be achieved in a number of ways (IV mannitol, MRIgFUS and bradykinins etc). With super selective catheterization, the drug’s volume of distribution (Vd) is restricted to a targetted area. Additionally, following drug delivery, flow may be arrested to prevent drug washout with blood flow.1 Continued...